PTH-122 A Retrospective Study to Compare the Effectiveness of Referral Methods to Alcohol Services for Specialist Treatment from an Acute Hospital following Brief Intervention. (4th June 2013) - Vardy, M; Day, E; Webb, K; Russell, C; Sudhakaran, P; Ahmad, I; Cobain, K; Aldulaimi, D
Abstract : Introduction: Screening, brief intervention and referral to treatment (SBIRT) programmes have been advocated as having a preventive effect in non dependent drinkers and can provide a pathway to access specialist treatment for alcohol use disorders (AUD) for hospitalised patients who are contemplating changing their drinking behaviour. Little research into the effect of referral methods in hospitalised people treated for AUDs has been carried out. Methods: Patient data for 2007–2009 were retrospectively reviewed in order to compare two referral to treatment methods namely, referral to treatment by a specialist nurse (RTT group) or self referral supported by a specialist nurse (SSR). Attendances at offered appointments were compared to identify each referral methods efficacy in eliciting attendance at a community alcohol treatment service following a request for further treatment for AUD elicited during hospitalisation in an acute setting. Results: The sample size was 76; the most common reason for hospitalisation was deliberate overdose with alcohol (17.3%) followed by fall or collapse with alcohol (11.8%) Alcoholic Liver Disease with alcohol withdrawal (7.3%). Of 76 Patients referred to treatment by both methods, 36 were in the SSR group and 40 in the RTT group, no significant difference in response to referral modality between the RTT and SSR group was detected. Conclusion: This study found no evidence of a difference in effectiveness of referral methods. This suggests that both referral methods were as effective as each other in eliciting attendance at a specialist alcohol treatment service after an offer of treatment had been made during acute hospitalisation. Further studies, with a larger population, are required to validate this finding Disclosure of Interest: None Declared.